A high-strength flame-retardant antistatic polyethylene polymer material and preparation process

By using a flame-retardant and antistatic cross-linking agent in polyethylene materials to chemically cross-link polyethylene grafted maleic anhydride and carboxylated graphene to form a continuous network structure, the problems of polyethylene materials' flammability and poor antistatic properties are solved. problem, achieving improvements in high strength, flame retardancy and antistatic properties.

CN118599204BActive Publication Date: 2025-01-21SHANDONG HONGLINXIANG ELECTROMECHANICAL EQUIP CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410819957.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-24
Publication Date
2025-01-21
Estimated Expiration
2044-06-24

AI Technical Summary

Technical Problem

Polyethylene materials are flammable and difficult to improve their flame retardancy and antistatic properties at the same time. The prior art conflicts in the modification process, resulting in a decline in the mechanical properties of the materials.

Method used

A flame retardant and antistatic cross-linking agent is used to chemically cross-link polyethylene grafted maleic anhydride and carboxylated graphene to form a continuous network structure and improve the flame retardant, antistatic and mechanical properties of the material.

Benefits of technology

It has improved the high strength, flame retardancy and antistatic properties of polyethylene materials, broadened its application fields, while maintaining the material's aging resistance and corrosion resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure QLYQS_1
    Figure QLYQS_1
  • Figure BDA0004908829640000051
    Figure BDA0004908829640000051
  • Figure BDA0004908829640000061
    Figure BDA0004908829640000061
Patent Text Reader

Abstract

The invention relates to the technical field of polyethylene polymer materials, and discloses a high-strength flame-retardant antistatic polyethylene polymer material and a preparation process. Hexamethylol melamine, 4-methoxyphenylphosphonic acid dichloride and 3-bromopropylene are used as raw materials to synthesize a flame-retardant antistatic crosslinking agent containing phosphorus and nitrogen elements. Hydroxyl groups and alkenyl groups on the surface of the flame-retardant crosslinking agent are chemically crosslinked with polyethylene, polyethylene grafted maleic anhydride and carboxyl groups of carboxylated graphene to form a continuous network structure, so that the phosphorus and nitrogen flame-retardant elements are stably present in the material and are not easy to migrate and precipitate. The quaternary ammonium salt cation in the structure has certain hygroscopicity and strong adhesion, and can form a single-molecule conductive film on the surface of the material. The increase in the crosslinking degree enables the graphene to adhere to the crosslinked network veins to form a relatively complete graphene conductive path, thereby enhancing the antistatic property and mechanical property of the material, and having good application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polyethylene polymer materials, in particular to a high-strength flame-retardant and antistatic polyethylene polymer material and a preparation process thereof. Background Art

[0002] Polyethylene is a typical thermoplastic and is the largest of the five general-purpose plastics. Polyethylene has excellent chemical stability and chemical corrosion resistance. It is also widely used in many fields due to its non-toxic, low density, light weight and low price. However, polyethylene has poor flame retardancy, produces droplets when burned, and generates a large amount of heat, which can easily cause the spread of flames. In addition, as a common polymer material, polyethylene has a very high resistivity. When it comes into friction with other objects, it is difficult to release the static charge generated inside the material. A lot of static charge will accumulate on the surface, which will affect the cleanliness of the material surface and even generate electric sparks to cause fire or explosion. This limits the application of polyethylene in many aspects. Therefore, flame retardant and antistatic modification of polyethylene has become an inevitable trend for future development.

[0003] In the prior art, the simplest way to improve the flame retardancy of polyethylene is to add flame retardants, the most common of which are halogen flame retardants and inorganic flame retardants. Halogen flame retardants have excellent flame retardancy, but they produce toxic gases when burned, which are harmful to the environment. Inorganic flame retardants have the characteristics of good stability, low toxicity, no corrosive gases, and long flame retardancy, but their disadvantage is that they generally require a large addition amount, which greatly deteriorates the mechanical properties of polyethylene. The antistatic agent used for polyethylene materials can generally be a conductive filler, such as conductive carbon black, which has the disadvantage of poor dispersibility and uneven dispersion of carbon black particles, resulting in a decrease in the mechanical properties of the product. Therefore, a large amount is required to meet the antistatic requirements.

[0004] In the prior art, the simultaneous flame retardant and antistatic modification of polyethylene is a complex physical and chemical process, and there is a conflict between the flame retardant modification and the antistatic modification; the additives added during the antistatic modification will promote the combustion of polyethylene, which will make the amount of flame retardant added during the dual anti-modification larger than that during the single flame retardant modification, and the large amount of flame retardant added will lead to the deterioration of the mechanical properties of the material, the deterioration of fluidity and other results; the present invention aims to synthesize a flame retardant and antistatic crosslinking agent, a crosslinking agent with flame retardant and antistatic functions, which can produce chemical crosslinking with polyethylene grafted with maleic anhydride and carboxylated graphene to form a continuous network structure, thereby improving the mechanical, flame retardant and antistatic properties of the polyethylene material. Summary of the invention

[0005] The technical problem solved by the invention is to provide a high-strength flame-retardant antistatic polyethylene polymer material and a preparation process, solve the problem of flammability of existing polyethylene polymer materials, and improve the antistatic and mechanical properties.

[0006] The technical solution of the present invention is:

[0007] A high-strength flame-retardant antistatic polyethylene polymer material comprises the following components in parts by weight: 100 parts of ultra-high molecular weight polyethylene, 10-25 parts of carboxylated graphene, 3-15 parts of a structural formula flame retardant and antistatic crosslinking agent, 4-8 parts of polyethylene grafted maleic anhydride, 0.8-1.5 parts of antioxidant and 0.1-1 parts of nucleating agent.

[0008] The antioxidant is any one of antioxidant 1010, antioxidant BHT or antioxidant 168.

[0009] The nucleating agent is any one of talc, silicon dioxide or zinc stearate.

[0010] Furthermore, the preparation process includes the following steps: mixing ultra-high molecular weight polyethylene, polyethylene grafted maleic anhydride, a nucleating agent and an antioxidant evenly in a double-roll open plasticizer at 110-120°C, then adding carboxylated graphene and a flame retardant and antistatic crosslinking agent, mixing for 10-20 minutes in an internal mixer at a temperature of 150-165°C and a speed of 50-100r / min, placing it in a flat vulcanizer for hot pressing, and cold pressing it into sheets at room temperature to obtain a high-strength flame retardant and antistatic polyethylene polymer material.

[0011] Furthermore, the hot pressing temperature is 170-185° C., the pressure is 5-15 MPa, and the time is 5-10 min.

[0012] Furthermore, the preparation process of the flame retardant antistatic crosslinking agent comprises the following steps:

[0013] Step S1, under a nitrogen atmosphere, add hexamethylol melamine and chlorobenzene to a reaction flask, stir evenly, add 4-methoxyphenylphosphonic dichloride, stir to react, filter after the reaction, wash with ethanol and deionized water, and dry to obtain intermediate 1.

[0014] Step S2, under a nitrogen atmosphere, add intermediate 1 and acetonitrile to a reaction flask, stir evenly, add 3-bromopropylene, stir to react, after the reaction is completed, filter, wash with acetonitrile, and dry to obtain intermediate 2.

[0015] Step S3, under a nitrogen atmosphere, add intermediate 2 and dichloromethane to a reaction flask, stir evenly, add boron tribromide, react at 0-20° C. for 12-24 h, add deionized water and ethyl acetate for extraction, concentrate the organic phase, and dry to obtain a flame retardant antistatic crosslinking agent.

[0016] Furthermore, in step S1, the molar amount of 4-methoxyphenylphosphonic dichloride is 310-350% of the molar amount of hexamethylol melamine.

[0017] Furthermore, in step S1, the reaction temperature is 85-100° C., and the reaction time is 8-16 h.

[0018] Furthermore, the molar amount of 3-bromopropylene in step S2 is 380-520% of the molar amount of the intermediate 1.

[0019] Furthermore, in step S2, the reaction temperature is 65-80° C., and the reaction time is 24-48 h.

[0020] Furthermore, the molar amount of boron tribromide in step S3 is 400-650% of the molar amount of intermediate 2.

[0021] The beneficial technical effects of the present invention are:

[0022] The invention uses hexamethylol melamine, 4-methoxyphenylphosphonic acid dichloride and 3-bromopropylene as raw materials to synthesize a flame retardant and antistatic crosslinking agent containing phosphorus and nitrogen elements, utilizes the hydroxyl and olefin groups on the surface of the flame retardant and antistatic crosslinking agent to generate chemical crosslinking with polyethylene, polyethylene grafted maleic anhydride and carboxyl groups of carboxylated graphene to form a continuous crosslinking network structure, and the obtained high-strength flame retardant and antistatic polyethylene polymer material has excellent flame retardant and antistatic properties, further broadening its application field.

[0023] When heated, the organic phosphorus contained in the flame retardant and antistatic crosslinking agent can decompose phosphoric acid to quickly form an expanded carbon layer on the surface of the material, preventing external heat from being transferred to the inside, reducing the heat absorbed by the internal material and slowing down the combustion rate; the triazine structure will produce gases such as NH3 and CO2 when burned, and at the same time promote the formation of carbon, inhibit oxygen and insulate, reduce the pyrolysis rate, and reduce the amount of flammable volatiles generated; the hydroxyl group in the flame retardant and antistatic crosslinking agent structure can react with the carboxyl chemical grafting of polyethylene grafted maleic anhydride and carboxyl graphene to form an interpenetrating crosslinking network, so that the flame retardant elements are more stably present in the polyethylene material and are not easy to migrate and precipitate, thereby improving the flame retardant properties of polyethylene composites.

[0024] The flame retardant and antistatic crosslinking agent contains quaternary ammonium salt cations, which have certain hygroscopicity and strong adhesion. It can form a single-molecule conductive film on the surface of the material to improve the conductive properties of the polyethylene material. At the same time, the carboxylated graphene can chemically bond with the hydroxyl group of the flame retardant and antistatic crosslinking agent, and crosslink with polyethylene through the olefin group of the flame retardant and antistatic crosslinking agent. The increase in the degree of crosslinking allows the graphene to adhere to the veins of the crosslinking network, forming a relatively complete graphene conductive path, improving the interface compatibility, and enhancing the antistatic properties of the material.

[0025] The polyethylene grafted maleic anhydride has structural similarity with polyethylene, and can improve the compatibility of the system. The acid anhydride group can produce a chemical grafting reaction with the carboxyl group of the carboxylated graphene and the hydroxyl group of the flame retardant and antistatic crosslinking agent to form an interpenetrating crosslinked network; at the same time, the triene group of the flame retardant and antistatic crosslinking agent can produce crosslinking with the polyethylene during the mixing process, and promote the further improvement of the crosslinked interpenetrating network structure; the polyethylene polymer material prepared by the invention has improved the flame retardant and antistatic effects while maintaining its mechanical properties, and does not affect the original excellent aging resistance and corrosion resistance of the polyethylene material, can be widely used in the fields of metallurgy, chemical industry, petroleum extraction, etc., and has a good application prospect. DETAILED DESCRIPTION

[0026] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the following are specific embodiments to further describe the present invention in detail. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0027] Preparation of polyethylene grafted maleic anhydride: Take 10g ultra-high molecular weight polyethylene and 50g xylene, stir evenly, add 0.1g dibenzoyl peroxide and 4g maleic anhydride, react at 80°C for 5h, filter, wash with ethanol, and dry to obtain polyethylene grafted maleic anhydride.

[0028] Preparation of carboxylated graphene: 100 mg of graphene was dispersed in 100 mL of deionized water and dispersed evenly by ultrasonication to obtain graphene oxide. 6 g of sodium hydroxide and 5 g of chloroacetic acid were added and ultrasonicated for 3 h to convert the hydroxyl and epoxy groups on the graphene oxide into carboxyl groups. The graphene oxide was filtered and dried to obtain carboxylated graphene.

[0029] Hexamethylol melamine, CAS number is 531-18-0.

[0030] 4-Methoxyphenylphosphonic acid dichloride, CAS number is 37632-18-1.

[0031] 3-Brompropylene, CAS number is 106-95-6.

[0032] Example 1

[0033] (1) Under nitrogen atmosphere, 35 mmol of hexamethylol melamine and 280 mL of chlorobenzene were added to a reaction flask, stirred evenly, and then 119 mmol of 4-methoxyphenylphosphonic acid dichloride was added. The mixture was reacted at 95° C. for 12 h, filtered, washed with ethanol and deionized water, and dried to obtain intermediate 1. The preparation process is as follows:

[0034]

[0035] (2) Under nitrogen atmosphere, 30 mmol of intermediate 1 and 400 mL of acetonitrile were added to a reaction flask, stirred evenly, and then 135 mmol of 3-bromopropylene was added. The mixture was reacted at 70° C. for 36 h, filtered, washed with acetonitrile, and dried to obtain intermediate 2. The preparation reaction formula is as follows:

[0036]

[0037] (3) Under nitrogen atmosphere, 28 mmol of intermediate 2 and 460 mL of dichloromethane were added to the reaction flask, and after stirring, 155 mmol of boron tribromide was added, and the mixture was reacted at 10° C. for 16 h. Deionized water and ethyl acetate were added for extraction, and the organic phase was concentrated and dried to obtain a flame retardant antistatic crosslinking agent. The preparation reaction formula is as follows:

[0038]

[0039] (4) 100 g of ultra-high molecular weight polyethylene, 6 g of polyethylene grafted maleic anhydride, 0.5 g of talc and 1.2 g of antioxidant 1010 were mixed evenly in a double-roll open plastic mill at 115°C, and then 12 g of carboxylated graphene and 3 g of flame retardant and antistatic crosslinking agent were added. The mixture was mixed in an internal mixer at a temperature of 155°C and a speed of 80 r / min for 15 min, and then placed in a flat vulcanizer for hot pressing at a hot pressing temperature of 180°C, a pressure of 10 MPa, and a time of 9 min. The sheet was cold pressed at room temperature to obtain a high-strength flame retardant and antistatic polyethylene polymer material.

[0040] Example 2

[0041] (1) Under nitrogen atmosphere, 60 mmol of hexamethylol melamine and 300 mL of chlorobenzene were added to a reaction flask. After stirring, 186 mmol of 4-methoxyphenylphosphonic acid dichloride was added. The mixture was reacted at 100° C. for 8 h. The mixture was filtered, washed with ethanol and deionized water, and dried to obtain intermediate 1.

[0042] (2) Under nitrogen atmosphere, 50 mmol of intermediate 1 and 600 mL of acetonitrile were added to a reaction flask. After stirring, 190 mmol of 3-bromopropylene was added. The mixture was reacted at 80° C. for 24 h. The mixture was filtered, washed with acetonitrile, and dried to obtain intermediate 2.

[0043] (3) Under nitrogen atmosphere, 45 mmol of intermediate 2 and 675 mL of dichloromethane were added to a reaction flask, and after stirring, 180 mmol of boron tribromide was added. The mixture was reacted at 20° C. for 12 h, and deionized water and ethyl acetate were added for extraction. The organic phase was concentrated and dried to obtain a flame retardant antistatic crosslinking agent.

[0044] (4) 100 g of ultra-high molecular weight polyethylene, 4 g of polyethylene grafted maleic anhydride, 0.1 g of silica and 0.8 g of antioxidant BHT were mixed evenly in a double-roll open plastic mill at 120° C., and then 15 g of carboxylated graphene and 6 g of flame retardant and antistatic crosslinking agent were added. The mixture was mixed in an internal mixer at a temperature of 165° C. and a speed of 100 r / min for 10 min, and then hot-pressed in a flat vulcanizer at a hot pressing temperature of 185° C., a pressure of 15 MPa, and a time of 5 min. The sheet was cold-pressed at room temperature to obtain a high-strength flame retardant and antistatic polyethylene polymer material.

[0045] Example 3

[0046] (1) Under nitrogen atmosphere, 35 mmol of hexamethylol melamine and 350 mL of chlorobenzene were added to a reaction flask. After stirring, 122.5 mmol of 4-methoxyphenylphosphonic acid dichloride was added. The mixture was reacted at 85° C. for 16 h. The mixture was filtered, washed with ethanol and deionized water, and dried to obtain intermediate 1.

[0047] (2) Under nitrogen atmosphere, 30 mmol of intermediate 1 and 450 mL of acetonitrile were added to a reaction flask. After stirring, 156 mmol of 3-bromopropylene was added. The mixture was reacted at 65° C. for 48 h. The mixture was filtered, washed with acetonitrile, and dried to obtain intermediate 2.

[0048] (3) Under nitrogen atmosphere, 25 mmol of intermediate 2 and 300 mL of dichloromethane were added to a reaction flask. After stirring, 162.5 mmol of boron tribromide was added. The mixture was reacted at 0° C. for 24 h. Deionized water and ethyl acetate were added for extraction. The organic phase was concentrated and dried to obtain a flame retardant antistatic crosslinking agent.

[0049] (4) 100 g of ultra-high molecular weight polyethylene, 8 g of polyethylene grafted maleic anhydride, 1 g of zinc stearate and 1.5 g of antioxidant 168 were mixed evenly in a double-roll open plastic mill at 110° C., and then 18 g of carboxylated graphene and 9 g of flame retardant and antistatic crosslinking agent were added. The mixture was kneaded in an internal mixer at a temperature of 150° C. and a speed of 50 r / min for 20 min. The mixture was placed in a flat vulcanizer for hot pressing at a temperature of 170° C., a pressure of 5 MPa and a time of 10 min. The mixture was cold pressed at room temperature to obtain a high-strength flame retardant and antistatic polyethylene polymer material.

[0050] Example 4

[0051] (1) Under nitrogen atmosphere, 120 mmol of hexamethylol melamine and 815 mL of chlorobenzene were added to a reaction flask. After stirring, 390 mmol of 4-methoxyphenylphosphonic acid dichloride was added. The mixture was reacted at 90° C. for 15 h. The mixture was filtered, washed with ethanol and deionized water, and dried to obtain intermediate 1.

[0052] (2) Under nitrogen atmosphere, 100 mmol of intermediate 1 and 1450 mL of acetonitrile were added to a reaction flask. After stirring, 480 mmol of 3-bromopropylene was added. The mixture was reacted at 75° C. for 35 h. The mixture was filtered, washed with acetonitrile, and dried to obtain intermediate 2.

[0053] (3) Under nitrogen atmosphere, 85 mmol of intermediate 2 and 1530 mL of dichloromethane were added to a reaction flask. After stirring, 495 mmol of boron tribromide was added. The mixture was reacted at 10° C. for 16 h. Deionized water and ethyl acetate were added for extraction. The organic phase was concentrated and dried to obtain a flame retardant antistatic crosslinking agent.

[0054] (4) 100 g of ultra-high molecular weight polyethylene, 7 g of polyethylene grafted maleic anhydride, 0.8 g of talc and 1.2 g of antioxidant 1010 were mixed evenly in a double-roll open plastic mill at 115° C., and then 22 g of carboxylated graphene and 12 g of flame retardant and antistatic crosslinking agent were added. The mixture was mixed in an internal mixer at a temperature of 160° C. and a speed of 80 r / min for 12 min, and then hot-pressed in a flat vulcanizer at a hot pressing temperature of 180° C., a pressure of 12 MPa, and a time of 8 min. The sheet was cold-pressed at room temperature to obtain a high-strength flame retardant and antistatic polyethylene polymer material.

[0055] Example 5

[0056] (1) Under nitrogen atmosphere, 15 mmol of hexamethylol melamine and 120 mL of chlorobenzene were added to a reaction flask. After stirring, 48 mmol of 4-methoxyphenylphosphonic acid dichloride was added. The mixture was reacted at 95° C. for 16 h. The mixture was filtered, washed with ethanol and deionized water, and dried to obtain intermediate 1.

[0057] (2) Under nitrogen atmosphere, 12 mmol of intermediate 1 and 168 mL of acetonitrile were added to a reaction flask. After stirring, 54 mmol of 3-bromopropylene was added. The mixture was reacted at 70° C. for 45 h. The mixture was filtered, washed with acetonitrile, and dried to obtain intermediate 2.

[0058] (3) Under nitrogen atmosphere, 10 mmol of intermediate 2 and 185 mL of dichloromethane were added to a reaction flask. After stirring, 55 mmol of boron tribromide was added. The mixture was reacted at 0° C. for 24 h. Deionized water and ethyl acetate were added for extraction. The organic phase was concentrated and dried to obtain a flame retardant antistatic crosslinking agent.

[0059] (4) 100 g of ultra-high molecular weight polyethylene, 7 g of polyethylene grafted maleic anhydride, 0.6 g of silica and 1.1 g of antioxidant BHT were mixed evenly in a double-roll open plastic mill at 120° C., and then 25 g of carboxylated graphene and 15 g of flame retardant and antistatic crosslinking agent were added. The mixture was mixed in an internal mixer at a temperature of 155° C. and a speed of 70 r / min for 20 min, and then placed in a flat vulcanizer for hot pressing at a temperature of 180° C., a pressure of 10 MPa, and a time of 10 min. The sheet was cold pressed at room temperature to obtain a high-strength flame retardant and antistatic polyethylene polymer material.

[0060] Comparative Example 1

[0061] 100 g of ultra-high molecular weight polyethylene, 6 g of polyethylene grafted maleic anhydride, 0.5 g of talc and 1.2 g of antioxidant 1010 were mixed evenly in a double-roll open plastic mill at 115° C., then 12 g of carboxylated graphene and 3 g of intermediate 2 (prepared by Example 1) were added, and the mixture was mixed in an internal mixer at a temperature of 155° C. and a speed of 80 r / min for 15 min. The mixture was placed in a flat vulcanizer for hot pressing at a temperature of 180° C., a pressure of 10 MPa, and a time of 9 min. The mixture was cold pressed into sheets at room temperature to obtain a polyethylene polymer material.

[0062] Comparative Example 2

[0063] 100 g of ultra-high molecular weight polyethylene, 6 g of polyethylene grafted maleic anhydride, 0.5 g of talc and 1.2 g of antioxidant 1010 were mixed evenly in a double-roll open plastic mill at 115° C., then 12 g of carboxylated graphene and 3 g of intermediate 1 (prepared by Example 1) were added, and the mixture was mixed in an internal mixer at a temperature of 155° C. and a speed of 80 r / min for 15 min. The mixture was placed in a flat vulcanizer for hot pressing at a temperature of 180° C., a pressure of 10 MPa, and a time of 9 min. The mixture was cold pressed into sheets at room temperature to obtain a polyethylene polymer material.

[0064] Comparative Example 3

[0065] 100g ultra-high molecular weight polyethylene, 6g polyethylene grafted maleic anhydride, 0.5g talc and 1.2g antioxidant 1010 were mixed evenly in a double-roll open plastic mill at 115°C, then 12g carboxylated graphene was added, and the mixture was mixed in an internal mixer at a temperature of 155°C and a speed of 80r / min for 15min, and then hot-pressed in a flat vulcanizer at a hot pressing temperature of 180°C, a pressure of 10MPa, and a time of 9min, and cold-pressed at room temperature to obtain a polyethylene polymer material.

[0066] Limiting oxygen index test: Referring to the standard GB / T 2406-1993 "Plastic combustion performance test method - oxygen index method", the obtained polyethylene polymer material was made into a test specimen with a size of 100×6.5×3mm, and the limiting oxygen index of the specimen was determined using an oxygen index meter.

[0067] Vertical burning grade test: The obtained polyethylene polymer material is made into a test specimen with a size of 125×12.5×3.5 mm, and the vertical burning grade of the specimen is measured by a vertical burning instrument.

[0068] Table 1 Flame retardant performance test

[0069]

[0070] It can be seen from the test results in the above table that the limiting oxygen index value of pure polyethylene in Comparative Example 3 is only 17.4%, and it fails to pass the UL-94 test, indicating that polyethylene is extremely flammable; with the increase of the content of the flame retardant and antistatic crosslinking agent, the flame retardant performance of the polyethylene material is gradually enhanced, wherein the limiting oxygen index in Example 5 is 32.1%, and the vertical combustion grade reaches V-0, which belongs to the level of flame retardant materials; this is because the organic phosphorus contained in the flame retardant and antistatic crosslinking agent can quickly form an expanded carbon layer on the surface of the material when decomposed by heat, preventing external heat from entering the material. The flame retardant and antistatic crosslinking agent can transfer heat to the inside of the material, reduce the heat absorbed by the internal material, and slow down the combustion rate; at the same time, the triazine structure will produce NH3, CO2 and other gases during combustion, and at the same time promote the formation of carbon, inhibit oxygen and insulate, reduce the pyrolysis rate, and reduce the amount of flammable volatiles generated; on the other hand, the hydroxyl group in the flame retardant and antistatic crosslinking agent structure can react with the carboxyl chemical grafting of polyethylene grafted maleic anhydride and carboxyl graphene to form an interpenetrating crosslinking network, so that the flame retardant elements are more stably present in the polyethylene material, not easy to migrate and precipitate, thereby improving the flame retardant properties of polyethylene composites.

[0071] Intermediate 2 in Comparative Example 1 and Intermediate 1 in Comparative Example 2 contain phosphorus and nitrogen flame retardant elements and have certain flame retardant ability, but do not contain hydroxyl groups and cannot produce chemical grafting reactions with polyethylene grafted maleic anhydride and the carboxyl groups of carboxylated graphene. They do not have cross-linked structures and have poor dispersibility, making their flame retardant effects inferior to those of the embodiments.

[0072] Antistatic performance test: Referring to the standard GB / T 1410-2006, the volume resistivity and surface resistivity of the sample were measured using a high insulation resistance meter.

[0073] Table 2 Antistatic performance test

[0074] Volume resistivity (Ω·cm) Surface resistivity(Ω) Example 1 <![CDATA[4.3×10 11 ]]> <![CDATA[9.1×10 9 ]]> Example 2 <![CDATA[1.2×10 10 ]]> <![CDATA[6.8×10 8 ]]> Example 3 <![CDATA[3.6×10 9 ]]> <![CDATA[2.7×10 7 ]]> Example 4 <![CDATA[6.9×10 8 ]]> <![CDATA[4.3×10 6 ]]> Example 5 <![CDATA[2.2×10 8 ]]> <![CDATA[1.5×10 6 <!-- 7 -->]]> Comparative Example 1 <![CDATA[8.4×10 12 ]]> <![CDATA[4.6×10 10 ]]> Comparative Example 2 <![CDATA[3.6×10 13 ]]> <![CDATA[2.5×10 11 ]]> Comparative Example 3 <![CDATA[5.3×10 16 ]]> <![CDATA[3.8×10 14 ]]>

[0075] It can be seen from the test results in the above table that with the increase of the content of flame retardant antistatic crosslinking agent and carboxylated graphene, the volume resistivity and surface resistivity of the polyethylene material are significantly reduced, wherein the volume resistivity in Example 4 is 6.9×10 8 Ω·cm, surface resistivity 4.3×10 6 Ω, which is significantly lower than that of Comparative Example 3. This is because, on the one hand, the flame retardant and antistatic crosslinking agent contains quaternary ammonium salt cations, which have certain hygroscopicity and strong adhesion, and can form a monomolecular conductive film on the surface of the material to improve the conductive properties of the polyethylene material; on the other hand, the carboxylated graphene can be chemically bonded to the hydroxyl group of the flame retardant and antistatic crosslinking agent, and crosslinked with polyethylene through the olefin group of the flame retardant and antistatic crosslinking agent. The increase in the degree of crosslinking allows the graphene to adhere to the veins of the crosslinked network, forming a relatively complete graphene conductive path, improving the interface compatibility, and enhancing the antistatic properties of the material.

[0076] Tensile strength test: refer to standard GB / T 1040-1992, use universal testing machine for testing, tensile speed is 50mm / min.

[0077] Impact strength test: refer to standard GB / T 1843-2008 and use impact strength testing machine for testing.

[0078] Table 3 Mechanical properties test

[0079] Tensile strength(MPa) <![CDATA[Impact strength (kJ / m 2 )]]> Example 1 22.3 20.6 Example 2 25.6 21.5 Example 3 27.4 23.0 Example 4 28.9 23.5 Example 5 27.5 22.9 Comparative Example 1 20.2 19.7 Comparative Example 2 16.8 17.1 Comparative Example 3 15.6 16.2

[0080] It can be seen from the test results in the above table that with the increase of the content of flame retardant and antistatic crosslinking agent, the degree of crosslinking with polyethylene is improved, thereby enhancing the crosslinking network structure of the system, improving the interface compatibility, and increasing the tensile strength and impact strength of the material, thereby making the prepared polyethylene material have the characteristics of high strength and high toughness, broadening its further application.

[0081] Of course, the present invention may have many other embodiments. Without departing from the spirit and essence of the present invention, technicians familiar with the field may make various corresponding changes and deformations based on the present invention, but these corresponding changes and deformations should all fall within the scope of protection of the present invention.

Claims

1. A high-strength flame-retardant antistatic polyethylene polymer material, characterized in that: The polyethylene polymer material comprises the following components in parts by weight: 100 parts of ultra-high molecular weight polyethylene, 10-25 parts of carboxylated graphene, and 3-15 parts of a structural formula Flame retardant and antistatic crosslinking agent, 4-8 parts of polyethylene grafted maleic anhydride, 0.8-1.5 parts of antioxidant and 0.1-1 parts of nucleating agent; The antioxidant is any one of antioxidant 1010, antioxidant BHT or antioxidant 168; The nucleating agent is any one of talc, silicon dioxide or zinc stearate; The preparation process of the flame retardant antistatic crosslinking agent comprises the following steps: Step S1, under a nitrogen atmosphere, add hexamethylol melamine and chlorobenzene to a reaction flask, stir evenly, add 4-methoxyphenylphosphonic dichloride, stir to react, filter after the reaction, wash with ethanol and deionized water, and dry to obtain intermediate 1; Step S2, under a nitrogen atmosphere, add intermediate 1 and acetonitrile to a reaction flask, stir evenly, add 3-bromopropylene, stir to react, filter after the reaction is completed, wash with acetonitrile, and dry to obtain intermediate 2; Step S3, under a nitrogen atmosphere, add intermediate 2 and dichloromethane to a reaction flask, stir evenly, add boron tribromide, react at 0-20° C. for 12-24 h, add deionized water and ethyl acetate for extraction, concentrate the organic phase, and dry to obtain a flame retardant antistatic crosslinking agent.

2. A process for preparing the high-strength flame-retardant antistatic polyethylene polymer material as claimed in claim 1, characterized in that: The preparation process comprises the following steps: uniformly mixing ultra-high molecular weight polyethylene, polyethylene grafted maleic anhydride, a nucleating agent and an antioxidant in an open plasticizer with a double roller at 110-120° C., then adding carboxylated graphene and a flame retardant and antistatic crosslinking agent, mixing for 10-20 minutes in an internal mixer at a temperature of 150-165° C. and a rotation speed of 50-100 r / min, placing in a flat vulcanizer for hot pressing, and cold pressing at room temperature to produce sheets to obtain a high-strength flame retardant and antistatic polyethylene polymer material.

3. The preparation process of the high-strength flame-retardant antistatic polyethylene polymer material according to claim 2 is characterized in that: The hot pressing temperature is 170-185° C., the pressure is 5-15 MPa, and the time is 5-10 min.

4. The high-strength flame-retardant antistatic polyethylene polymer material according to claim 1, characterized in that: The molar amount of 4-methoxyphenylphosphonic dichloride in step S1 is 310-350% of the molar amount of hexamethylol melamine.

5. The high-strength flame-retardant antistatic polyethylene polymer material according to claim 1, characterized in that: In step S1, the reaction temperature is 85-100° C. and the reaction time is 8-16 hours.

6. The high-strength flame-retardant antistatic polyethylene polymer material according to claim 1, characterized in that: The molar amount of 3-bromopropylene in step S2 is 380-520% of the molar amount of the intermediate 1.

7. The high-strength flame-retardant antistatic polyethylene polymer material according to claim 1, characterized in that: In step S2, the reaction temperature is 65-80° C. and the reaction time is 24-48 hours.

8. The high-strength flame-retardant antistatic polyethylene polymer material according to claim 1, characterized in that: The molar amount of boron tribromide in step S3 is 400-650% of the molar amount of intermediate 2.

Citation Information

Patent Citations

  • Antistatic flame-retardant ultra high molecular weight polyethylene composition and preparation method thereof

    CN102432939A

  • Phosphorus-containing network structure flame retardant

    CN106832963A